Kajian Jenis-Jenis Kalimat Dalam Sintaksis: Studi Kasus Pada Film Dora And The Lost City Of Gold - Saadah, Siti Waliyatus (PT. Alahyan Publisher Sukabumi, 2023)
This study aims to understand the types of sentences in language learning because it can help learners understand how to build and use sentences correctly and effectively. In addition, understanding sentence types can also help enrich vocabulary and sentence structures used in daily communication. In this study, the film